STRATEGI PEMASARAN DESA WISATA KOTA PARI KECAMATAN PANTAI CERMIN KABUPATEN SERDANG BEDAGAI - Tina Taviani (Akademi Pariwisata Darma Agung, 2023)
This study aims to explore the marketing strategy of Kota Pari Tourism Village in Pantai Cermin District, Serdang Bedagai Regency, Indonesia. This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Respondents were selected by purposive sampling method and consisted of tourism village managers, local entrepreneurs and tourists. The results of the study show that the marketing strategy of Pari City Tourism Village includes the use of social media, cooperation with local entrepreneurs, participation in promotional events, and good management of tourist destinations. In addition, this research also shows that factors such as cleanliness, safety, and comfort are very important in attracting tourists. This research makes an important contribution to the development of Kota Pari Tourism Village and can be a reference for managers of other tourist villages in designing effective marketing strategies